Effect of time of using feed blocks as supplementary feed on the weightchanges and reproductive performance of Awassi yearling ewes depend on crop residues as basal diet - Ibrahim, Hadeel K. (The Iraqi Journal of Veterinary Medicine, 2005)
This study was conducted to evaluate the Effect of time of using feedblocks (FB) as supplementary feed on the weight changes and reproductiveperformance of Awassi yearling ewes depend on crop residues as basal diet. .Sixty Awassi yearling ewes (mean live weight 39.51 kg) aged 12-13 monthswere allocated into four groups according to their live weight. First group (T1)fed conventional diet (barley grains + straw). The second group (T2) fedconventional diet plus FB during pre and post mating. The third group (T3) fedconventional diet plus FB during pre and mating. The fourth group (T4) fedconventional diet plus FB during post mating. The results of this experimentshowed that using FB as supplementary feed reduced the weight losses ofAwassi yearling ewes. FB supplementation improved conception rate of Awassiyearling ewes as compared with control group (T1). The T2 group had thehighest conception rate (86.66%) followed by T3 and T4 (73.33%) and thelowest group T1 (66.66%). Using FB during pre mating (T2, T3) reducedmating season of Awassi yearling ewes were 70-82% of these lambed from 1stcycle. Lambing percentage increased considerably due to FB supplementation.The lambing percentages were 100, 87, 80 and 73% for groups T2, T3, T4 andT1 respectively.